Antithetical modes of and the Ca2+ sensors targeting in ANF-RGC and ROS-GC1 membrane guanylate cyclases - Duda, Teresa; Peretzev, Alexandre; Koch, Karl-Wilhelm; Sharma, Rameshwar K. (Frontiers in Molecular Neuroscience, 2012)
The membrane guanylate cyclase family has been branched into three subfamilies: natriuretic peptide hormone surface receptors, Ca2+-modulated neuronal ROS-GC, and Ca2+-modulated odorant surface receptor ONE-GC. The first subfamily is solely modulated by the extracellularly-generated hormonal signals; the second, by the intracellularly-generated sensory and sensory-linked signals; and the third, by combination of these two. The present study defines (1) a new paradigm and (2) a new mechanism of Ca2+ signaling. (1) ANF-RGC, the prototype member of the surface receptor subfamily, is stimulated by free [Ca2+]i. The stimulation occurs via myristoylated form of neurocalcin , and both the guanylate cyclase and the calcium sensor neurocalcin are present in the glomerulosa region of the adrenal gland. (2) The EF-2, EF-3 and EF-4 hands of GCAP1 sense the progressive increment of [Ca2+]i and with a K1/2 of 100 nM turn ROS-GC1 “OFF”. In total reversal, the same EF hands upon sensing the progressive increment of [Ca2+]i with K1/2 turn ONE-GC “ON”. The findings suggest a universal Ca2+-modulated signal transduction theme of the membrane guanylate cyclase family; demonstrate that signaling of ANF-RGC occurs by the peptide hormones and also by [Ca2+]i signals; that for the Ca2+ signal transduction, ANF-RGC functions as a two-component transduction system consisting of the Ca2+ sensor neurocalcin  and the transducer ANF-RGC; and that the neurocalcin  in this case expands beyond its NCS family. Furthermore, the study shows a novel mechanism of the [Ca2+]i sensor GCAP1 where it acts as an antithetical NCS for the signaling mechanisms of ROS-GC1 and ONE-GC.